Anti-Bullying Socialization as an Effort to Prevent Bullying Cases in the Elementary School Environment at SDN 1 Sukahaji - Ratna Dewi; Rohendi R; Didih Ahmadiah (Yayasan Daarul Huda Kruengmane, 2025)
Bullying remains a serious issue frequently found in elementary school environments and can negatively affect students’ psychological, social, and character development. As the early stage of formal education, elementary school plays an important role in shaping children’s personality and social attitudes. However, students’ limited understanding of the forms, impacts, and prevention of bullying causes such behavior to persist and is often perceived as harmless joking. This community service program aimed to improve students’ understanding and awareness of bullying prevention through an anti-bullying socialization activity. The program was conducted by KPM students at SDN 1 Sukahaji through preparation, implementation, and evaluation stages using observation and interactive discussions. The results showed an improvement in students’ understanding of the types of bullying, its negative impacts, and prevention strategies, while also encouraging mutual respect and the courage to report bullying incidents. This socialization activity is expected to contribute to creating a safe and bullying-free elementary school environment.